How to use COVID-19 antiviral drugs in patients with chronic kidney disease - Kale, Ajinath; Shelke, Vishwadeep; Dagar, Neha; Anders, Hans-Joachim; Gaikwad, Anil Bhanudas (Frontiers in Pharmacology, 2023)
Antiviral drugs such as Remdesivir (Veklury), Nirmatrelvir with Ritonavir (Paxlovid), Azvudine, and Molnupiravir (Lagevrio) can reduce the risk for severe and fatal Coronavirus Disease (COVID)-19. Although CKD is a highly prevalent risk factor for severe and fatal COVID-19, most clinical trials with these drugs excluded patients with impaired kidney function. Advanced CKD is associated with a state of secondary immunodeficiency (SIDKD), which increases the susceptibility to severe COVID-19, COVID-19 complications, and the risk of hospitalization and mortality among COVID-19 patients. The risk to develop COVID-related acute kidney injury (AKI) is higher in patients with precedent CKD. Selecting appropriate therapies for COVID-19 patients with impaired kidney function is a challenge for healthcare professionals. Here, we discuss the pharmacokinetics and pharmacodynamics of COVID-19-related antiviral drugs with a focus on their potential use and dosing in COVID-19 patients with different stages of CKD. Additionally, we describe the adverse effects and precautions to be taken into account when using these antivirals in COVID-19 patients with CKD. Lastly, we also discuss about the use of monoclonal antibodies in COVID-19 patients with kidney disease and related complications.